Hubungan Penerapan Sanitasi Total Berbasis Masyarakat (STBM) dengan Perilaku BAB dan CTPS Masyarakat Desa Caturharjo, Sleman, Yogyakarta Tahun 2013 - Muslikah Muslikah; Sri Puji Ganefati; Purwanto Purwanto (Poltekkes Kemenkes Yogyakarta, 2014)
One effort to increase community awareness and behavior in sanitation services is the applica-tion of community-led total sanitation (CLTS), which one of its pillars is stop defecation carelessly and washing hands with soap. Caturharjo Village in Sleman District has implemented CLTS program since 2012, and the all hamlets had conducted the triggering activity. However, some people were not participated. The purpose of the study was to determine the relationship bet-ween the application of CLTS and community behavior in defecation and washing hands, by conducting an observational study with cross-sectional survey design. 330 family heads were se-lected as sample and respondents, and were obtained by using simple random sampling tech-nique. Data were collected by questionnaire and check-list, and subsequently were analysed by chi-square test at 95 % signifcance level. The results showed that among people who were in-volved in CLTS triggering activity, 92,7 % did not defecate carelessly, and 86,7 % washed their hands with soap. To conclude, the CLTS program has significant relationship with both beha-viors.